2022
DOI: 10.1111/os.13490
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of a Smile‐Necklace Plate for Treating Inferior Patellar Pole Avulsion Fractures: A Review and Hypothesis

Abstract: The patella's inferior pole transmits force generated by contraction of the quadriceps muscle to the tibial tuberosity through the attached patellar ligament, thus completing knee extension. Therefore, fractures of the patella's inferior pole disrupt the coherence of mechanical transmission in the lower extremities. There appears to be no consensus among trauma centers regarding the treatment of infrapatellar pole fractures, primarily because there is no consistent design or application of internal fixation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The elastic modulus and Poisson’s ratio of bones and steel wires in the model were defined based on previous research (as shown in Table 1 ) ( Du et al, 2022 ). Frictional contact was set between the periphery of the patella and bone tunnel wire, as well as between the patella and vertical wire, with a friction coefficient of 0.2 ( Zhu et al, 2022 ). The friction coefficient of the fractured end of the inferior pole of the patella was set to 0.45 ( Chang et al, 2018 ; Demirtaş and Kati, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The elastic modulus and Poisson’s ratio of bones and steel wires in the model were defined based on previous research (as shown in Table 1 ) ( Du et al, 2022 ). Frictional contact was set between the periphery of the patella and bone tunnel wire, as well as between the patella and vertical wire, with a friction coefficient of 0.2 ( Zhu et al, 2022 ). The friction coefficient of the fractured end of the inferior pole of the patella was set to 0.45 ( Chang et al, 2018 ; Demirtaş and Kati, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, when steel wires are inserted into the fractured comminuted area at the inferior pole, it can result in weak fixation and potential displacement of small bone fragments. This increases the risk of internal fixation failure and nonunion ( Zhu et al, 2022 ; Fan et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various parameters of the bone and wire in the 3D model were defined, such as the elastic modulus and Poisson’s ratio (as shown in Table 1 ) [ 4 ]. Three types of frictional contacts were set: the contact between the periphery of the patella and encircling wire, contact between the patella and vertical wire with a friction coefficient of 0.2 [ 23 ], and contact between fracture ends with a friction coefficient of 0.45 [ 24 , 25 ]. The portion where the wire passed through the patella was set as “bonded” (i.e., there was no relative displacement between them).…”
Section: Methodsmentioning
confidence: 99%